The effects of inhibiting IRE1α on the viability of ovarian granulosa cells - Li, Chao; Tan, Yong-Peng; Meng, Tie-Gang; Gao, Di; Xu, Ke; Lu, You-Hui; Yi, Li-Tao; Liu, Shu-Chen; Wang, Guang; Sun, Qing-Yuan; Lei, Xiao-Can (Scientific reports, 2025)
IRE1α, a type I transmembrane protein characterized by a cytoplasmic serine/threonine kinase domain, is related to ER stress and ER function maintenance. In this study, 4µ8c, a highly effective selective inhibitor of IRE1α RNase, and APY29, an ATP competitive inhibitor, inhibiting IRE1α autophosphorylation and the kinase domain, were employed to elucidate the function of IRE1α on the proliferation of ovarian granulosa cells, with the ultimate goal of identifying novel strategies and methodologies for the prevention and treatment of associated diseases. Human ovarian granulosa cells (SVOG) cultured in vitro were treated with the IRE1α inhibitors 4µ8c and APY29. It was shown that inhibition of IRE1α reduced the cell ability of dealing with misfolded protein, triggered oxidative stress, altered mitochondrial membrane potential, and inflicted DNA damage, eventually lead to ovarian granulosa cell apoptosis.